Development of A Website-Based Guidance and Counseling Orientation Management Model - Bukahares, Henny; Dwikurnaningsih, Yari (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2024)
The objective of the research is to develop a website-based Guidance and Counseling orientation management model. This research method uses Research and Development (R&D) with the Borg & Gall model. The subjects of the study are school principals, guidance and counseling teachers and students. The data collection techniques used are interviews, observations and document studies. The data from the research results were analyzed using a mixture of quantitative and qualitative methods. This research produced a guidance and counseling management model with the name Mission Biking Bae which is an acronym for Mission – Orientation Management, Biking – Counseling Guidance, Bae – Website-Based.  Based on the results of expert validation and field trials, it shows that the Biking Bae Mission model is in the good category and is worth using. The results of the validation of IT experts were 77% and guidance and counseling experts were 76%. The results of the field trial on 30 students, 2 guidance and counseling teachers and the principal were 87%, 82% and 85% respectively. Thus, the Biking Bae Mission model can be used by guidance and counseling teachers and students to increase the effectiveness of guidance and counseling services in schools.